The Characteristic of Online Transportation Services and Provision in Semarang City - Dewi, Novi Kartika; Rakhmatulloh, Anita Ratnasari (Jurnal Teknik Sipil dan Perencanaan, 2018)
The complex mobility in Semarang city requires the efficient and effective provision and services of public transportation. Due to the condition of public transportation services is not proper, so it requires the presence of online transportation. Online transportation services have a flexibility (in routes and time) and it seems the society has their own private vehicles. Online transportation prices is more expensive than private vehicles or public transportation. But it provides flexibility and convenience as one of the alternative transportation mode.